Evaluating the Implementation of Mover Teacher Education Program of English Language Teachers in West Nusa Tenggara - Untung Waluyo; Sudirman Wilian; Sudirman Sudirman (Journal of Languages and Language Teaching, 2023)
The Mover Teacher Program (MTP), released in 2021, is widely regarded as a crucial measure towards achieving substantial transformations in the field of education in Indonesia. The present study aims to evaluate the effectiveness of the MTP in Sumbawa Besar City. Through this study, we sought evidence of lessons learnt from the field. To conduct the study, researchers employed a modified version of Kirkpatrick’s evaluation model. Three out of four postulates derived from the model were used to probe the phenomenon under investigation, i.e. (1) teachers’ reaction, (2) learning endeavor and (3) application of knowledge/skills gained. The fourth postulate regarding the assessment of students’ achievement was not included in the study as the MTP program just commenced in the research site. The study employed a qualitative research approach with a multiple-case design. Participants of this study were eight alumni of MTP teachers coming from four different schools. Data were collected through interviews, observations and study of related documents. The data collected were analyzed thematically through data reduction, data presentation, conclusion drawing and verification. Results of the study show that participants of the study benefitted from participating in the MTP program although they underwent various route of transformational learning. Regardless of disorienting problem in the beginning of the program implementation, participants were able to maintain their new skills and knowledge to improve their own teaching performance and other teachers in the impacted schools. The participants experienced transformation of learning and behavioral change after participating in the long and exhausting MTP program.